PENGARUH DISIPLIN KERJA, SEMANGAT KERJA DAN KOMPENSASI TERHADAP KINERJA PEGAWAI PADA SEKRETARIAT DPRD KABUPATEN BUTON UTARA - Rizal Adi Saputra; Patwayati Patwayati; Sinarwati Sinarwati; Eliyanti Agus Mokodompit; Abd. Razak Yusuf; La Ode Kalimin; Isalman Isalman (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine and analyze the effect of work discipline, spirit at work and compensation on employee performance in Secretariat of the Regional Representative Council of North Buton Regency. The research approach is quantitative. The population of this study was 35 employees of Secretariat of the Regional Representative Council of North Buton Regency. The number of samples used was 35 people with census techniques. The collected data was analyzed using Partial Least Square (PLS) using the SmartPLS M3 Ver. 2The results of the analysis show that work discipline has a positive and significant effect on employee performance with a parameter coefficient value of 0.282853, which means that the better work discipline then the resulting performance will be better. Spirit at work has a positive and significant influence on employee performance with a parameter coefficient of 0.293047, which means that the better the perceived spirit at work will have an impact on the resulting increase in performance. Compensation has a positive and significant effect on employee performance with a parameter coefficient of 0.400234, which means that the better the compensation given then will have an impact on the better performance produced.